2017
DOI: 10.1002/adma.201702115
|View full text |Cite
|
Sign up to set email alerts
|

Isoindigo‐Based Polymers with Small Effective Masses for High‐Mobility Ambipolar Field‐Effect Transistors

Abstract: So far, most of the reported high-mobility conjugated polymers are p-type semiconductors. By contrast, the advances in high-mobility ambipolar polymers fall greatly behind those of p-type counterparts. Instead of unipolar p-type and n-type materials, ambipolar polymers, especially balanced ambipolar polymers, are potentially serviceable for easy-fabrication and low-cost complementary metal-oxide-semiconductor circuits. Therefore, it is a critical issue to develop high-mobility ambipolar polymers. Here, three i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
131
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 60 publications
3
131
0
Order By: Relevance
“…[17] In addition, the fully locked backbone of LPPV may lead to stronger electronic coupling between adjacent units and lower effective mass (m*), and finally boost the intrachain charge transport. [18] Figure 2d shows the calculated band structures and density of states (DOS) of the LPPV backbone. LPPV exhibits large dispersion of the conduction band energy and asmall m e *(m*of an electron) of 0.130 m e .T he calculation of spin density distribution on an egatively charged polymer hexamer indicated that the anion polaron is well delocalized along the conjugated backbone in LPPV (Figure 2e).…”
Section: Angewandte Chemiementioning
confidence: 92%
“…[17] In addition, the fully locked backbone of LPPV may lead to stronger electronic coupling between adjacent units and lower effective mass (m*), and finally boost the intrachain charge transport. [18] Figure 2d shows the calculated band structures and density of states (DOS) of the LPPV backbone. LPPV exhibits large dispersion of the conduction band energy and asmall m e *(m*of an electron) of 0.130 m e .T he calculation of spin density distribution on an egatively charged polymer hexamer indicated that the anion polaron is well delocalized along the conjugated backbone in LPPV (Figure 2e).…”
Section: Angewandte Chemiementioning
confidence: 92%
“…Ambipolar conjugated polymers, which transport holes and electrons simultaneously, have great potential in simple and low cost fabrication of light emitting field‐effect transistors (FETs) and complementary‐like inverter through one‐step printing process . The most effective way to realize ambipolar polymers is copolymerization of an electron donor and acceptor unit (D–A) having the same charge transport capability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, introducing fluorine atoms to the molecular backbone usually brings about additional van der Waals interactions and helps to create planar conjugated backbones and stronger intermolecular interactions, which are generally beneficial for improving charge transport . For example, copolymers based on DPP, isoindigo, and rylene diimides as acceptors and fluorinated thiophenes as donors, exhibit ambipolar transport behavior with ultra‐high hole and electron mobilities, respectively …”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] For example, copolymers based on DPP,i soindigo, and rylene diimides as acceptors and fluorinated thiophenes as donors, exhibit ambipolar transport behavior with ultra-high hole and electron mobilities, respectively. [40][41][42] While there has been growingi nterest in the chlorination strategy that has recently emergeda sa nother promising option to tune the electronicp roperties. It hasb een verified that chlorine atom offers certain advantageous properties relative to fluorine atom, including easier synthetic accessibility, lower cost of precursors, and empty 3d orbitals that can facilitate p-electrons delocalization.…”
Section: Introductionmentioning
confidence: 99%